Elementary Teachers’ Perception of Language Skills: Student Skills and Learning Strategy - Susilawati, Susilawati; Hadianti, Yeni; Ruqoyyah, Siti; Mufidah, Zulfin Rachma (KnE Social Sciences, 2025)
Language skills are an important aspect in the development of education in elementary schools because this ability influences students’ academic achievement and social abilities. Language skills that elementary school students must master include listening, speaking, reading, and writing skills.Therefore, teachers must understand the extent of language skills each elementary school student possesses. This research aims to explore teachers’ perceptions of the language skills possessed by students in elementary schools, as well as the challenges faced in the teaching process. The research method used is descriptive qualitative, with data collection through interviews. Participants in this research were 15 elementary school teachers in West Bandung. The research results show that the majority of teachers have a positive perception of the importance of language skills in students. However, teachers also expressed challenges in implementing effective learning strategies, such as limited time, lack of appropriate teaching materials, and differences in language abilities among students. This study suggests the need for ongoing training for teachers and the development of teaching materials that better suit students’ needs. In conclusion, teachers’ perceptions of language skills are very important in determining learning success, but further support is still needed in terms of resources and learning methods.